Diccionario Berlitz plus Español Inglés - Inglés Español - Berlitz Publishing Company (Colombia : Grupo Editorial Norma, 1993)
This dictionary has been designed to take account or your practical nedds. Unnecesary linguistic information has been avoided. The entries are listed in alphabetical order regardless of whether the entry word is printed in a single word or in two or more separate words.
Contenido 1. Guía de pronunciación 2. Menu reader 3. Spanish abbreviations 4. Numerals 5. Time 6. Measures and temperature 7. some basic phrases 8. Léxico gastronómico 9. Verbos irregulares ingleses 10. Abreviaturas inglesas 11. Numerals 12. La horra 13. Medidas y temperatura 14. Algunas expresiones útiles
Incluye indice
Keywords: ENCICLOPEDIAS Y DICCIONARIOS -- DICCIONARIOS DE INGLÉS; ESPAÑOL - DICCIONARIO - INGLÉS